The real ornaments of the language - Pardayeva Kholida (Proceedings of The ICECRS, 2020)
It is seemed to easy to understand what is a collocation, what is compound words, and what is an idiom for us. But there are various difficulties throughout for using them. We can obtain to differentiate them only studying, analyzing, and realizing. We know that it is covered up the words and word combinations of our lives. These are helped once more natural and sensible our worlds. Using properly collocations and compounds will also help you to increase your range of English vocabulary